2015
DOI: 10.1371/journal.pone.0115372
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 (GDF-15) Plasma Levels Increase during Bleomycin- and Cisplatin-Based Treatment of Testicular Cancer Patients and Relate to Endothelial Damage

Abstract: IntroductionChemotherapy-related endothelial damage contributes to the early development of cardiovascular morbidity in testicular cancer patients. We aimed to identify relevant mechanisms of and search for candidate biomarkers for this endothelial damage.MethodsHuman micro-vascular endothelial cells (HMEC-1) were exposed to bleomycin or cisplatin with untreated samples as control. 18k cDNA microarrays were used. Gene expression differences were analysed at single gene level and in gene sets clustered in biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…Etoposide, camptothecin and doxorubicin also caused a similar increase in IAP gene expression (Figure S5A). In addition, analysis of other microarray data sets (Altena et al, 2015; Hussner et al, 2012) revealed that induction of IAP genes after doxorubicin or cisplatin treatment occurs in other cancerous (HeLa, Figure S5B) and primary (HMEC-1, Figure S5C) cell lines. Together these results suggest that induction of IAP proteins by DNA damaging agents is not limited to cisplatin or HCT116 cells (Figure S5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…Etoposide, camptothecin and doxorubicin also caused a similar increase in IAP gene expression (Figure S5A). In addition, analysis of other microarray data sets (Altena et al, 2015; Hussner et al, 2012) revealed that induction of IAP genes after doxorubicin or cisplatin treatment occurs in other cancerous (HeLa, Figure S5B) and primary (HMEC-1, Figure S5C) cell lines. Together these results suggest that induction of IAP proteins by DNA damaging agents is not limited to cisplatin or HCT116 cells (Figure S5A–C).…”
Section: Resultsmentioning
confidence: 99%
“…GDF-15 is also known to participate in vascular pathological processes [21]. In a preclinical model for chemotherapyinduced endothelial damage its genes were highly upregulated [22]. GDF-15 thus seems to reflect endothelial activation during chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we identified growth differentiation factor-15 (GDF-15), also known as macrophage inhibitory cytokine-1, as a clinically valuable marker for predicting progression to microalbuminuria and macroalbuminuria in both T2D and hypertension patients (2), suggesting that GDF-15 may be a valuable marker for individual risk stratification in patients with normoalbuminuria and microalbuminuria. Although GDF-15 can be upregulated in diverse tissues in response to damage, circulating levels of GDF-15 appear to reflect primarily damage to the vascular endothelium (3)(4)(5). In addition to GDF-15, we later demonstrated in the same cohort of patients that the cardiac biomarker high-sensitivity troponin T (hs-TnT) also predicted the worsening of albuminuria in both T2D and hypertension (6).…”
mentioning
confidence: 80%